(untitled) (Research, Society and Development, 2020)
Drug abuse is a major public health problem that causes a range of harm to users, both physical and psychological. In the physical field, systemic and oral changes are notable. Drug use among young people and adults, a phenomenon known as drug addiction, has been established in increasingly early age groups in recent decades. The objective of the present study was to evaluate the oral condition, nutrition and quality of life of users of illicit drugs who are undergoing treatment in the Detoxification Ward of the Hospital Universitário from Paraná West. For this purpose, structured questionnaires and oral clinical examinations were used to identify the conditions associated with the use of such substances. The results showed that the majority of the volunteers evaluated presented important oral alterations, mainly caries. They hava a predominantly cariogenic diet and low salivary flow. Conclusion: It is concluded that it is important that drug addicts have being accompanied by a dentist because the dependence directly affects the oral cavity, reducing the patient’s self-esteem and recovery.